Malaysian public perception towards airline safety factors and issues - Ahmad Nabil Saroni (Kulliyyah of Information and Communication Technology, International Islamic University Malaysia, 2020)
In recent years, there were several unfortunate incidents that have diminished the reputation and public perception of airline safety in Malaysia. The country's airline industry was hardly hit particularly by the mysterious occasion of Malaysia Airlines Flight MH370, the downing of Malaysia Airlines Flight MH17 due to missile attacks, and the demotion of Malaysia's air safety rating into Category 2 by the Federal Aviation Administration (FAA) of United States. Accordingly, this research sought to understand the current Malaysian public perception towards airlines safety factors and issues. A research conceptual framework was established for both data collection and analysis purposes. Research data was gathered by using a self-developed questionnaire via an online survey. A total of 110 respondents participated in the online survey, however, only 102 responses were retained and usable for the data analysis. There were 5 airline safety factors and 3 airline safety issues investigated in the study. From the analysis, a number of safety factors and issues were revealed as more dominant and had larger correlations with Malaysian public perception towards airline safety in comparison to others. Nonetheless, public concerns on airline safety remains essential due to the emerging threats and critical nature of the industry. In view of that, airlines are expected to unfailingly respond to those threats in order to ensure their survival in what is already a fiercely competitive industry.